HUBUNGAN PARITAS IBU DENGAN KEJADIAN PARTUS LAMA DI RSUD PROF. DR. MARGONO SOEKARJO PURWOKERTO TAHUN 2013 - Tin Utami (Viva Medika, 2014)
The purpose of this study was to determine the relationship of maternal parity with the incidence of prolonged labor in the District General Hospital Prof. Dr. Margono Soekarjo Purwokerto in 2013. This research method is analytic correlation with case control approach. This study uses secondary data derived from medical records of patients at the General Hospital of Prof. Dr. Margono Soekarjo Purwokerto. Sampling using quota sampling number 50 case samples and 50 control samples. Analysis of the data used were univariate ie only see the picture of the distribution of variable frequency and bivariate analysis using chi square. The results of this study is no relationship between maternal parity with the incidence of prolonged labor. (Î¡value = 0.0001 <0.05). In get the value of OR = 24.438, meaning that parity primiparous and grandemultipara can cause the incidence of prolonged labor 24.438 times higher than parity multiparas. The conclusion of this research that there is a relationship between parity with the incidence of prolonged labor in hospitals Prof. Dr. Margono Soekarjo 2013 Keywords: parity, prolonged labor.